Human-Plant Interactions in Semi-Arid Regions: An Archaeobotanical Study of the Iron Age Site of Mtanye, Southwestern Zimbabwe - Mushangwe, Cornelius Taurai (Department of Archaeology, 2020)
Humans have always interacted with plants for thousands of years ago. The origin of plant domestication is a clear example of human-plant mutualism. This mutual relationship has gradually developed into a co-entangled relationship where both symbionts benefit each other in an environment. The evidence of this relationship is confirmed by the use of plants across the globe, which constitutes a critical component in the livelihoods of people. It is likely to have been the case during the Iron Age period in Southern Africa, particularly in southwestern Zimbabwe where diversity of plant resources and other economic activities supported the Early farming communities in a variety of ways. Unfortunately, the available information about plant use, the role of crops and wild plants beyond diet and subsistence is widely dispersed. Studies that adequately analyse plant remains from Early Iron Age sites to understand the purpose of plants especially wild in the daily livelihoods of early farming communities is lagging. The labour and decision making invested in the selection, management, gathering, processing and consumption of these plants is not known. This research explored an analysis of archaeobotanical remains at Mtanye site, one of the early farming communities in Gwanda, southwestern Zimbabwe. Ethnobotanical and archaeobotanical techniques, as well as further microscopic analysis of seeds in the laboratory, were performed. The assessment of ethnobotanical examinations and archaeobotanical remains concluded that plants were vital to Mtanye community’s daily livelihoods, by offering an essential contribution to social, religious and economic development in the face of environmental challenges. The people at Mtanye treated crop cultivation and gathering of wild plants with more considerable ingenuity just like other sectors of their economies. Considering that the environment was not conducive for adequate crop farming, the intensive use of wild plant resources likely underpinned their ability to survive in a semi-arid environment for a prolonged time.